Analysis of Dynamic Damage-Induced Porosity Changes of Granites in Leaching Mining Technique Based on SHPB Test. (9th September 2020) - Miao, Yichen; Liu, Changwu; He, Zhiliang; Ma, Yuanjun; Wu, Haikuan; Wang, Ding
Abstract : In situ leaching was a very important technical approach in ion-adsorption rare earth mining, because it can effectively avoid the geological hazards, protect the environment, and reduce the mining costs. The critical issue of this mining technique was to increase the permeability of ion-adsorption rare earth deposits. Due to the close relationship between the permeability and the porosity, in this paper, several experiments were conducted to find the dynamic characteristics of the granite deposit and the relationship between the dynamic characteristics and the porosity. Moreover, the SHPB test system was equipped to conduct the dynamic test, and the ultrasonic wave detector with high precision was employed to obtain the damage factor of granites. The test results showed that the failure mode under dynamic load and static load was close, and they both had splitting failure. Besides, when cyclic dynamic loading velocity was between 5.8 m/s and 8.4 m/s, the specimen was not a failure, but it caused the damage and changed the porosity. And the dynamic thresholds of failure stress and damage stress were found. Finally, a linear relationship between the porosity and the damage factor was found, which would help to analyze and predict the change of porosity under different dynamic loading velocities.